Integrated approach for the assessment of the benthic ecosystem functioning at a coastal site in the northern Adriatic Sea. (15th June 2016) - Franzo, Annalisa; Cibic, Tamara; Del Negro, Paola
Abstract: The assessment of an ecosystem functioning is very complex and requires an integrated approach based on the combined and synoptic estimates of biological processes and the study of communities at different trophic levels. Here we present the main results gained over a 2 year-period aimed to investigate the benthic ecosystem functioning at a virtually pristine coastal site. Our suggested approach follows consecutive and interconnected steps: from the chemical characterisation of the sediments to the evaluation of the main autotrophic and heterotrophic metabolic processes, passing through the study of microphytobenthos and meiofauna. Our results indicate that in summer the system experienced pulsed inputs of fresh organic matter mostly due to the proliferation of benthic diatoms. This freshly produced material increased the sediment nutritional value supporting higher meiofaunal densities and stimulating benthic prokaryotes in mobilising C and incorporating it in new biomass. In winter, the lower availability of fresh organic matter, mainly due to the lower diatom abundances, contributed to a reduced prokaryotic C reworking and overall to a major confinement of C flow within the benthic microbial loop. The system shifted from net autotrophy to net heterotrophy as a response to temperature and light variations at the bottom. The latter factors directly influence the microalgal photosynthetic efficiency and are therefore responsible for the observed uncoupling between microphytobenthic abundances and primary production rates. Highlights: A pristine system showed naturally occurring fluctuations over a 2 year-period. Net autotrophy of the system was observed with low temperature only. In summer diatom proliferation seemed to increase labile organic matter. Its availability stimulated prokaryotic activity enhancing C transfer to meiofauna. In winter, C was mainly sequestered within the benthic microbial loop.